Pengaruh Lingkungan Bahasa terhadap kemampuan Berbicara Bahasa Arab - Rifky Rosian An Nur; Baiq Tuhfatul Unsi (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2021)
Abstract: Language is a habit that is easy to control and master. Language becomes part of human behavior which is shaped and influenced by the surrounding environment. speaking skills aim to make students able to communicate verbally properly and naturally with the language they are learning. Dulay explained that the language environment is very important for a learner to be successful in learning a new language (a second language). The focus of this study was to determine the effect of the language environment on students' speaking ability in Arabic. The research method used is a quantitative method. The results of this study are: 1. The Arabic language environment at MTs Salafiyah Syafi'iyah Tebuireng Jombang is quite good with a percentage of 66.88%. 2. The ability to speak Arabic for grade VIII students of MTs Salafiyah Syafi'iyah Tebuireng Jombang is quite good with a percentage of 59.2%. 3. There is a significant influence between the language environment on the ability to speak Arabic. With the value of T count = 3.812 greater than T table = 2,000 and the probability value (a) 0.000 <0.05, then Ho is rejected and Ha is accepted. This means that the language environment is very influential on the speaking ability of students of Mts Salafiyah Syafi'iyah Tebuireng Jombang. Keyword: Language environment, Speaking ability